PENINGKATAN KOMPETENSI GURU MELALUI PELATIHAN PEMBUATAN MODUL PEMBELAJARAN SMK NIBA BUSINESS SCHOOL - Endaryono, Bakti Toni; Noor, Gena Prasetya; Rifai, Nurdin; Susilo, Herman (LPPM Universitas Sangga Buana, 2025)
Research approach carried out with the aim of solving problems by teachers in the context of learning, with the benefits of improving the quality of learning, improving teacher profesionalism, adjusting learning methods, creating a better learning environment and as a means of teacher evaluation and self-reflection. The purpose of this community service activity in addition to the Tri dharma activities of lecturers is to provide teachers with a deep understanding of, and provide teacher skills on making learning modules at SMK NIBA Business School. This activity method uses the PAR (Participatory Action Research) method with a lecture approach, discussion with the FGD (Focus Group Discussion) strategy by involving the participation of activity participants, namely teachers, education personnel and students. This community service activity is carried out with 4 steps which include (1) providing material about PTK, (2) providing discussion opportunities for participants, (3) participants are given practice in making learning modules and (4) participants are given guidance on compiling reports on the results of class action research activities. The results of this community service activity are (1) the achievement of goals about teachers understanding in depth about classroom action research and understanding about the PTK cycle. (2) teachers are able to create creative learning module designs with the SAM (Successive Approximation Model) design model (3) Teachers are able to create constructivism-based learning. The conclusion of this community service activity is that educators (teachers) at SMK NIBA Business School are able to understand improve teacher competence in making creative learning modules.